The Regenerative Potential of Female Skeletal Muscle upon Hypobaric Hypoxic Exposure - Mancinelli, Rosa; Di Filippo, Ester S.; Verratti, Vittore; Fulle, Stefania; Toniolo, Luana; Reggiani, Carlo; Pietrangelo, Tiziana (Frontiers in Physiology, 2016)
Aim: The aim of this study was to determine whether a 14-day trekking expeditions, in high altitude hypoxic environment, triggers redox disturbance at the level of satellite cells (adult stem cells) in young women. Methods: We collected muscle biopsies from Vastus Lateralis muscle for both single fiber analysis and satellite cells isolation. The samples collected before (PRE-Hypoxia) and after (POST-Hypoxia) the trekking in the Himalayas were compared. Satellite cells were investigated for oxidative stress (oxidant production, antioxidant enzyme activity and lipid damage), mitochondrial potential variation, gene profile of HIF and myogenic transcription factors (Pax7, MyoD, myogenin) and miRNA expression (miR-1, miR-133, miR-206). Results: The nuclear domain analysis showed a significant fusion and consequent reduction of the Pax7+ satellite cells in the single mature fibers. The POST-Hypoxia myoblasts obtained by two out of six volunteers showed high superoxide anion production and lipid peroxidation along with impaired dismutase and catalase and mitochondrial potential. The transcription profile and miRNA expression were different for oxidized and non oxidized cells. Conclusions: The present study supports the phenomenon of hypobaric-hypoxia-induced oxidative stress and its role in the impairment of the regenerative capacity of satellite cells derived from the Vastus Lateralis muscle of young adult female subjects.